Controlling for Endogeneity of Strike Variables in the Estimation of Wage Settlement Equations - Jimenez‐Martin, Sergi (Journal of Labor Economics, 1999)
This article analyzes wage changes with an unbalanced panel from the Spanish Collective Bargaining in Large Firms survey. Central to the analysis are the joint determination of strike and wage outcomes and, in particular, the estimation of the slope of the wage concession curve. I control for the possible endogeneity of strike variables in the wage equation and suggest two sets of instruments: lagged strike outcomes or reduced‐form predictions of the strike variables. When controlling for endogeneity, a negative relationship between strike duration and the size of the wage change arises. However, short strikes still produce higher wage changes.